2020
DOI: 10.1101/2020.12.02.404004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triggering closure of a sialic acid TRAP transporter substrate binding protein through binding of natural or artificial substrates

Abstract: The pathogens Vibrio cholerae and Haemophilus influenzae use tripartite ATPindependent periplasmic transporters (TRAPs) to scavenge sialic acid from host tissues. They use it as a nutrient or to evade the innate immune system by sialylating surface lipopolysaccharides. An essential component of TRAP transporters is a periplasmic substrate binding protein (SBP). Without substrate, the SBP has been proposed to rest in an open-state, which is not recognised by the transporter. Substrate binding induces a conforma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Both crystallography and single-molecule Förster-resonance energy transfer (smFRET) experiments on the single SBD1 and SBD2 showed that substrate binding was linked to a conformational change of the corresponding SBD from an open apo conformation to a closed liganded conformation [18][19][20][21]. The results also implied an induced-fit-type ligand-binding mechanism, where conformational dynamics are induced by ligand-SBD interactions similar as later also demonstrated for other SBPs [22][23][24][25][26]. Additionally, it was shown that the opening of the SBDs and ligand release was the rate-limiting step in the transport cycle and that the closed conformation triggers ATP-hydrolysis and transport [18].…”
Section: Introductionsupporting
confidence: 58%
“…Both crystallography and single-molecule Förster-resonance energy transfer (smFRET) experiments on the single SBD1 and SBD2 showed that substrate binding was linked to a conformational change of the corresponding SBD from an open apo conformation to a closed liganded conformation [18][19][20][21]. The results also implied an induced-fit-type ligand-binding mechanism, where conformational dynamics are induced by ligand-SBD interactions similar as later also demonstrated for other SBPs [22][23][24][25][26]. Additionally, it was shown that the opening of the SBDs and ligand release was the rate-limiting step in the transport cycle and that the closed conformation triggers ATP-hydrolysis and transport [18].…”
Section: Introductionsupporting
confidence: 58%
“…The conformational dynamics between the open-and closed-states of SBPs have only recently been studied for ABC-transporter related SBPs 14,16,31 and were completely unknown for TRAP transporter SBPs. Our above described FRET experiments and kinetic analysis reveal that VcSiaP has a ligand dependent substrate-binding rate.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used single-molecule Förster-resonance energy transfer (smFRET) spectroscopy to investigate this important step of the mechanism by real-time measurements of VcSiaP dynamics under more physiological conditions. Such experiments should allow comparisons to SBPs from the ABC transporter family 14,17 . For this purpose, we employed the Q54C/L173C double mutant of VcSiaP that was used for the PELDOR/DEER experiments 18 .…”
Section: Open-closed Dynamics Of Vcsiap At Room Temperaturementioning
confidence: 99%
See 2 more Smart Citations